2021
DOI: 10.29219/fnr.v65.6254
|View full text |Cite
|
Sign up to set email alerts
|

L-arabinose and D-xylose: sweet pentoses that may reduce postprandial glucose and insulin responses

Abstract: Background: Diets inducing high fluctuations in plasma glucose levels are linked to type 2 diabetes. L-arabinose and D-xylose have been hypothesized to inhibit intestinal sucrase activity, delay sucrose digestion, and reduce glycaemic and insulinaemic responses. However, few human studies have assessed this using realistic foods. Objective: We investigated the effects of the addition of L-arabinose and D-xylose on glucose homeostasis using a fruit-based drink and the effect of L-arabinose using a muffin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
(77 reference statements)
1
11
0
Order By: Relevance
“…This resulted in an estimated sample size of minimal 20 participants. Previous studies from our lab [ 13 , 14 ] showed dropout rates of 17% and 11%. Taking into account a safe dropout rate of 20%, it was decided to enrol 24 subjects.…”
Section: Methodsmentioning
confidence: 83%
See 4 more Smart Citations
“…This resulted in an estimated sample size of minimal 20 participants. Previous studies from our lab [ 13 , 14 ] showed dropout rates of 17% and 11%. Taking into account a safe dropout rate of 20%, it was decided to enrol 24 subjects.…”
Section: Methodsmentioning
confidence: 83%
“…Sample size estimations were performed with the software program G-power (University of Kiel, Kiel, Germany). For all calculations, a paired Student’s t -test was assumed, with a two-tailed t -test with α = 0.05, power = 0.8, and SD of 0.75 mmol/L (obtained from previous experiments [ 13 , 14 ]). Furthermore, an effect of 0.5 mmol/L was assumed to be relevant in this population, which means an effect size (dz) of 0.67.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations